Sistem Jual Beli Pupuk Kandang Prespektif Imam Syafi’i dan Imam Hanafi (Studi di Kampung Sulusuban Kecamatan Seputih Agung) - Ahmad Mukhlishin; Saipudin Saipudin (Institut Agama Islam Ma'arif NU (IAIMNU) Metro Lampung, Indonesia, 2017)
Abstract This article is about buying and selling manure in Kampung Sulusuban Seputih Agung Subdistrict. In Kampung Sulusuban Kecamatan Septih Agung Lampung Tengah many pera farmers who can process and make Animal Manure as a reliable organic fertilizer, although manure is unclean and disgusting stuff that is livestock manure but in practice the fertilizer can fertilize agricultural crops and restore the soil structure that Has begun to become barren .. Though buying and selling of this unclean goods is an issue of controversy among scholars, especially between Syafi'i madhab with Madhab Hanafi. The focus of the study of this article is: how is the legal status of the sale and purchase in terms of comparative madhab between imam syafi'i and Imam Hanafi ? This article uses qualitative analysis with Islamic legal approach. The nature of this research is descriptive-analysis that is by describing the legal basis of the scholars in deciding cases of buying and selling unclean goods. Keywords: Sale and Purchase, Manure, Imam Syafi'i, Imam Hambali